PICTURE WORD INDUCTIVE MODEL (PWIM): Improving Students’ Ability in Writing a Descriptive Paragraph - Herlinawati Herlinawati (Universitas Lancang Kuning, 2014)
The focus on this research was to find out the effect of using Picture Word Inductive Model(PWIM) in writing a descriptive paragraph. This quasi experimental research focuses on writing ability. Thepopulation was the eighth students with the total students were 282 students. The sample was students in class VIII.1 consisted of 29 students as experiment class and VIII.2 with 28 students as control class. The instrument of data collecting was test. The test was used to get the data of students’ writing ability. The technique of data analysis uses T-test which was analyzed by using SPSS 17.0 for windows. Based on the data analysis, the researcher found that there was significant effect between students’ writing ability taught by using Picture Word Inductive Model (PWIM) and with the students who were taught using conventional way, with t-test calculation was 3.518 and t-table in significant level 5% = 2.00 and significant level 1%=2.65. It shows the t-test is higher than Sig.point 5% and 1%. 2.00<3.518>2.65. As well, in Levenes’ test analysis, the Sig.(2-tailed) was 0.01. This significant point was 0.001 lower than 0.005. It means Ho was rejected and Ha was accepted. As the conclusion, the Picture Word Inductive Model (PWIM) gave low effectiveness of students’ writing ability for the eight grade students at SMPN 06 Pekanbaru.